2020
DOI: 10.1089/aut.2019.0002
|View full text |Cite
|
Sign up to set email alerts
|

Including Speaking and Nonspeaking Autistic Voice in Research

Abstract: Autistic individuals frequently report that their experiences are minimized or reinterpreted by well-meaning nonautistic parents, researchers, educators, and allies. Although the inclusion of autistic voice is improving, obstacles persist, particularly in research with individuals who might be described as non-or minimally speaking. In this perspective piece, I present three arguments: (1) ableist assumptions and practices that equate speaking voice with rational voice have led to the exclusion of autistic voi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…The project was not without its challenges and both the patient partners and the research management team identified several key areas in need of improvement, reassessment and reexamination. Future collaborative research initiatives need to adopt more flexible and inclusive practices so that adults from across the autism spectrum can be truly involved and engaged in research, and have their voices and perspectives heard [60]. Nevertheless, in remaining faithful to POR's core principles, the CONNECT model proved its potential to make research more accessible and more relevant to members of the autistic adult community.…”
Section: Resultsmentioning
confidence: 99%
“…The project was not without its challenges and both the patient partners and the research management team identified several key areas in need of improvement, reassessment and reexamination. Future collaborative research initiatives need to adopt more flexible and inclusive practices so that adults from across the autism spectrum can be truly involved and engaged in research, and have their voices and perspectives heard [60]. Nevertheless, in remaining faithful to POR's core principles, the CONNECT model proved its potential to make research more accessible and more relevant to members of the autistic adult community.…”
Section: Resultsmentioning
confidence: 99%
“…The research and development which is required to determine targeted, effective ways for elevating choline consumption and identifying personalized intake baselines sufficient for fulfilling physiological need for choline in this population is considerable. As with any autism research, investigations should purposefully include representatives and researchers with an autism diagnosis who can help to shape such interventions optimally for autistic children and adults (Chown et al, 2017;Hoekstra et al, 2018;Lebenhagen, 2019;Cascio et al, 2020;Hogan et al, 2020).…”
Section: Targeting Cholinergic and Gaba-ergic Signaling Pathways May mentioning
confidence: 99%
“…Although there is increasing community involvement in research, autistic individuals with communication differences, such as those who are non-speaking or minimally-speaking (Lebenhagen, 2020 ) and those with a learning disability (Long and Clarkson, 2017 ) are less well-represented in this movement (e.g., in Fletcher-Watson et al, 2019 ; Pavlopoulou, 2020 and Cassidy et al, 2021b , the authors noted that their projects were not fully inclusive of these individuals). Importantly, people with communication differences may require personalized support, unique modes of communication, and well-planned engagement for their voices to be heard (Long and Clarkson, 2017 ; Long et al, 2017 ; Lebenhagen, 2020 ). Without the use of these personalized approaches, communication differences can result in autistic people facing exclusion from processes of consultation and research (Long and Clarkson, 2017 ) due to communicative normativity (see Lebenhagen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, people with communication differences may require personalized support, unique modes of communication, and well-planned engagement for their voices to be heard (Long and Clarkson, 2017 ; Long et al, 2017 ; Lebenhagen, 2020 ). Without the use of these personalized approaches, communication differences can result in autistic people facing exclusion from processes of consultation and research (Long and Clarkson, 2017 ) due to communicative normativity (see Lebenhagen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%